2020
DOI: 10.32996/ijllt.2020.1.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Development And Validation Of Strategic Intervention Materials (SIMs) Of The Selected Topics In Trigonometry Of Precalculus Discipline In Senior High School

Abstract: Shaped with Vygotsky’s Principle on Scaffolding, this study aimed to develop and validate learning materials known as Strategic Intervention Materials (SIMs) of the selected topics in Trigonometry in the STEM strand. This developmental study undertook three phases, namely: planning, development, and validation and guided by the ADDIE Model in the data analysis. In the planning stage, the least-mastered competencies (LMC) were selected based on the results of their final examination in Pre-Calculus in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…By focusing on personal growth and development, ipsative assessment helps mathematics teachers identify their strengths and weaknesses, develop a deep understanding of their teaching styles, and establish realistic goals for continued improvement (O'Leary, 2019). This heightened awareness enables mathematics teachers to make informed decisions about their instructional strategies, adapt their teaching practices according to individual student needs, and ultimately enhance student learning outcomes (Luzano, 2020).…”
Section: Enhanced Self-awareness and Reflective Capacitymentioning
confidence: 99%
“…By focusing on personal growth and development, ipsative assessment helps mathematics teachers identify their strengths and weaknesses, develop a deep understanding of their teaching styles, and establish realistic goals for continued improvement (O'Leary, 2019). This heightened awareness enables mathematics teachers to make informed decisions about their instructional strategies, adapt their teaching practices according to individual student needs, and ultimately enhance student learning outcomes (Luzano, 2020).…”
Section: Enhanced Self-awareness and Reflective Capacitymentioning
confidence: 99%
“…As to what model to be used in developing a programmed instruction such as modules, Rogayan and Dollete (2019), Anunobi, et al (2017), and Luzano (2020 all suggested that the ADDIE model creates effective material due to its clear and specific nature. Since this study developed a programmed instruction, which was offline e-modules, the ideas found in the mentioned literature served as its guiding light.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Prabowo, et al (2018) stated that among the four competencies (Algebra, Calculus, Geometry and Trigonometry, and Statistics and Probability) tested in the National Examination in 2016 at the high school level, Trigonometry was the least mastered by learners. In a local study published by Luzano (2020), he stated that learners consider Trigonometry more difficult compared to other subjects of Mathematics.…”
Section: Introductionmentioning
confidence: 99%